2016
DOI: 10.1105/tpc.16.00286
|View full text |Cite
|
Sign up to set email alerts
|

SMAX1-LIKE7 signals from the nucleus to regulate shoot development in Arabidopsis via partially EAR motif-independent mechanisms

Abstract: Strigolactones (SLs) are hormonal signals that regulate multiple aspects of shoot architecture, including shoot branching. Like many plant hormonal signaling systems, SLs act by promoting ubiquitination of target proteins and their subsequent proteasome-mediated degradation. Recently, SMXL6, SMXL7, and SMXL8, members of the SMAX1-LIKE (SMXL) family of chaperonin-like proteins, have been identified as proteolytic targets of SL signaling in Arabidopsis thaliana. However, the mechanisms by which these proteins re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
184
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(203 citation statements)
references
References 43 publications
(128 reference statements)
14
184
1
Order By: Relevance
“…Remarkably, D53 is a homologue of SMAX1, suggesting that as with KAI2 and D14, different members of the same protein family mediate separable SL and KL signalling activities. Recent studies in Arabidopsis have shown that the co-orthologues of D53, SMAX1-LIKE6 (SMXL6), SMXL7 and SMXL8, have conserved roles as SL targets in the regulation of development (Soundappan et al, 2015; Wang et al, 2015; Liang et al, 2016). This suggests the attractive hypothesis that the SL signalling pathway evolved through duplication and diversification of proteins both upstream and downstream of MAX2.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, D53 is a homologue of SMAX1, suggesting that as with KAI2 and D14, different members of the same protein family mediate separable SL and KL signalling activities. Recent studies in Arabidopsis have shown that the co-orthologues of D53, SMAX1-LIKE6 (SMXL6), SMXL7 and SMXL8, have conserved roles as SL targets in the regulation of development (Soundappan et al, 2015; Wang et al, 2015; Liang et al, 2016). This suggests the attractive hypothesis that the SL signalling pathway evolved through duplication and diversification of proteins both upstream and downstream of MAX2.…”
Section: Introductionmentioning
confidence: 99%
“…D53 is another member of the SMXL family, all of which share similarity to the ClpB/HEAT SHOCK PROTEIN 100 (HSP100) class of heat shock proteins. In Arabidopsis, three D53 homologues (SMXL6, SMXL7 and SMXL8) act redundantly to mediate all tested strigolactonerelated components of MAX2 function (Soundappan et al 2015;Liang et al 2016;Bennett et al 2016). This redundancy might explain why suppressor screens for the increased shoot branching phenotype of max2 had not uncovered this protein family.…”
Section: : the Smxl Familymentioning
confidence: 99%
“…Hydrolysis might also serve as a mechanism for destroying the strigolactone ligand and deactivating the signal. At least in vitro, the hydrolysis product is slowly released, suggesting (Wang et al 2015;Liang et al 2016), but a physical association between KAI2 and SMAX1/SMXL2 is only inferred genetically. In this model, the specific ligand-substrate-repressor associations explain the observed physiological outcomes.…”
Section: Kai2 and D14 Are Both Receptor Proteins And Enzymesmentioning
confidence: 99%
“…Using a powerful mechanistic approach, Liang et al (2016) provide direct, in planta evidence in support of this D14-mediated SL signaling pathway. First, they assessed the subcellular localization of SMXL7 by fusing it to a fluorescent reporter gene and expressing it in Nicotiana benthamiana epidermal cells, finding that it strongly localized to the nucleus.…”
mentioning
confidence: 99%
“…Adult shoot morphology in smxl max2 (left) and max2 (right) mutants untransformed (upper panels) and overexpressing SMXL7 (lower panels). (Reprinted from Liang et al [2016] nanometers of each other, a distance sufficiently close for molecular interactions to occur. SMXL7 localized to speckles in the nucleus, and D14 appeared to be recruited to these speckles in response to treatment with a synthetic SL analog.…”
mentioning
confidence: 99%